Development of a formalism of movable cellular automaton method for numerical modeling of fracture of heterogeneous elastic-plastic materials - S. Psakhie; E. Shilko; A. Smolin; S. Astafurov; V. Ovcharenko (Fracture and Structural Integrity)
A general approach to realization of models of elasticity, plasticity and fracture of heterogeneous materials within the framework of particle-based numerical methods is proposed in the paper. It is based on building many-body forces of particle interaction, which provide response of particle ensemble correctly conforming to the response (including elastic-plastic behavior and fracture) of simulated solids. Implementation of proposed approach within particle-based methods is demonstrated by the example of the movable cellular automaton (MCA) method, which integrates the possibilities of particle-based discrete element method (DEM) and cellular automaton methods. Emergent advantages of the developed approach to formulation of many body interaction are discussed. Main of them are its applicability to various realizations of the concept of discrete elements and a possibility to realize various rheological models (including elastic-plastic or visco-elasticplastic) and models of fracture to study deformation and fracture of solid-phase materials and media. Capabilities of particle-based modeling of heterogeneous solids are demonstrated by the problem of simulation of deformation and fracture of particle-reinforced metal-ceramic composites.